Effect of Dual Phase Heat Treatment on Mechanical Properties of Vacuum Carburized Powder Metallurgy Steel Parts - Pamuk, Özer (Fırat University, 2025)
In this study, the effects of Dual Phase (DP) heat treatment applied to vacuum carburized Powder Metallurgy (PM) steel parts on mechanical properties were investigated. Different heat treatments consisting of Sintering (S), Normalization (N), Vacuum Carburizing (VC), DP and Tempering (T) heat treatments were applied to the produced PM parts. Subsequently, mechanical tests and characterization studies were carried out. N1 sample, which was applied only S heat treatment, exhibited 103.3 HV1.0 hardness, 189 MPa three-point bending strength and 3% uniform elongation. VC heat treatments improved the mechanical properties of the parts. N2 sample, which was applied to S+N+VC heat treatment, exhibited surface hardness of 537.31 HV1.0, center hardness of 182.13 HV1.0 and three-point bending strength of 243 MPa, but did not show ductility. A dual phase microstructure consisting of martensite in the surface regions and ferrite + martensite phases in the central regions of vacuum carbide-treated samples was successfully produced with DP heat treatment. It was determined that the martensite phase exhibited a homogeneous distribution in the microstructure. DP heat treatment increased the mechanical properties of the samples but decreased their ductility. The highest mechanical properties after the DP heat treatment were obtained in the N6 sample, which was applied to the S+N+VC+DP750 heat treatment process. This sample exhibited a surface hardness of 572.28 HV1.0, center hardness of 196.90 HV1.0 and three-point bending strength of 319 MPa. As a result of the data obtained within the scope of this study, it was concluded that the mechanical properties were improved with the DP heat treatment applied to the surface carburized PM steel parts.

Bu çalışmada, vakum karbürlenmiş Toz Metalurjisi (T/M) çelik parçalara uygulanan Çift Faz (ÇF) ısıl işleminin mekanik özelliklere etkileri araştırılmıştır. Üretilen T/M parçalara Sinterleme (S), Normalizasyon (N), Vakum Karbürleme (VK), ÇF ve Temperleme (T) ısıl işlemlerinden oluşan farklı ısıl işlemler uygulanmıştır. Devamında mekanik testler ve karakterizasyon çalışmaları gerçekleştirilmiştir. Sadece S ısıl işlemi uygulanan N1 numunesi 103,3 HV1,0 sertlik, 189 MPa üç nokta eğme dayanımı ve %3 üniform uzama sergilemiştir. VK ısıl işlemi parçaların mekanik özelliklerini geliştirmiştir. S+N+VK ısıl işlemleri uygulanan N2 numunesi 537,31 HV1,0 yüzey, 182,13 HV1,0 merkez sertlikleri ve 243 MPa üç nokta eğme dayanımı sergilemiş ancak süneklik göstermemiştir. Vakum karbürlenmiş numunelerin yüzey bölgelerinde martenzit, merkez bölgelerinde ise ferrit + martenzit fazlarından oluşan çift faz mikroyapısı ÇF ısıl işlemi ile başarılı bir şekilde üretilmiştir. Martenzit fazının mikroyapıda homojen bir dağılım sergilediği tespit edilmiştir. ÇF ısıl işlemi numunelerin mekanik özelliklerini arttırmış ancak sünekliklerini azaltmıştır. ÇF ısıl işlemi sonrası en yüksek mekanik özellikler, S+N+VK+ÇF750 ısıl işlemleri uygulanan N6 numunesinde gerçekleşmiştir. Bu numune, 572,28 HV1,0 yüzey sertliği, 196,90 HV1,0 merkez sertliği ve 319 MPa üç nokta eğme dayanımı sergilemiştir. Bu çalışma kapsamında elde edilen veriler neticesinde yüzey karbürlenmiş T/M çelik parçalara uygulanan ÇF ısıl işlemi ile mekanik özelliklerin geliştirildiği sonucuna ulaşılmıştır.
Vakum Karbürlenmiş Toz Metalurjisi Çelik Parçalara Uygulanan Çift Faz Isıl işleminin Mekanik Özelliklere Etkisi
Keywords: Metals and Alloy Materials; Metaller ve Alaşım Malzemeleri; Powder Metallurgy; Toz Metalurjisi; Materials Engineering (Other); Malzeme Mühendisliği (Diğer)